2015
DOI: 10.1158/1535-7163.mct-14-0983
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Expression as a Predictive Biomarker in Cancer Immunotherapy

Abstract: The resurgence of cancer immunotherapy stems from an improved understanding of the tumor microenvironment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
1,587
6
9

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,918 publications
(1,621 citation statements)
references
References 89 publications
19
1,587
6
9
Order By: Relevance
“…Challenges exist including appropriate trial design, patient selection, dose determination, and complex pharmacokinetics (11). Several potential biomarkers have emerged including programmed death-ligand 1 (PD-L1) or PD-1 expression (12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Although PD-L1 expression has been linked to poor prognoses and better therapeutic responses, its true predictive value is still unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Challenges exist including appropriate trial design, patient selection, dose determination, and complex pharmacokinetics (11). Several potential biomarkers have emerged including programmed death-ligand 1 (PD-L1) or PD-1 expression (12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Although PD-L1 expression has been linked to poor prognoses and better therapeutic responses, its true predictive value is still unknown.…”
mentioning
confidence: 99%
“…Although PD-L1 expression has been linked to poor prognoses and better therapeutic responses, its true predictive value is still unknown. Biomarker validation has been confounded by ex vivo results from histologic studies using different antibodies and positive or negative staining thresholds (15). There is an explicit need for molecular imaging tools that can noninvasively capture and quantify the spatiotemporal expression profiles of cancer-associated immune checkpoints.…”
mentioning
confidence: 99%
“…Similar issues have been observed in solid malignancies, where the use of PD-L1 as a biomarker is confounded by detection antibodies, differing cutoffs and differences in tissue preparation and processing variability. 75 It is also likely that biological behavior and prognosis are determined not only by overall PD-1 + TILs and tumor cells, but by functionally distinct subsets. PD-1 + numbers correlated with CD4 + T-cell and FoxP3 + numbers and GrB and TIA-1 + cells in several studies, 42,52,72 and similar associations were found between distribution patterns of FoxP3 + and PD-1 + cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of biomarkers is most advanced for cancer so it is worthwhile considering the current status in Emerging data indicate that this therapy is most effective in patients with tumours that highly express PD-L1 144 which can be assessed immunohistochemically within the tumour biopsy 146 . However, patients with PD-L1 low tumours also respond well to anti-PD-L1 therapy 143,145,146 . Despite early promise, the implementation of PD-L1 as a predictive biomarker remains problematic but it does serve as a model for the general approach now being taken within the cancer field -parallel development of therapy and biomarker.…”
Section: Cancermentioning
confidence: 99%